2022
DOI: 10.21891/jeseh.1059283
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Augmented Reality Applications in Biology Lesson on Academic Achievement and Motivation

Abstract: In this study, it was aimed to determine the effect of activities based on augmented reality applications in 9th grade biology lesson on students' achievement and motivation towards biology lesson and to get students' opinions about the applications. In the study, mixed method was used. The study group of the research consisted of students of two different classes at the 9th grade level of a private high school located in the city center of Karaman in the 2018-2019 academic year. When the research findings wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 75 publications
2
1
0
Order By: Relevance
“…These findings are in line with the research of which found that there were differences in the learning motivation of students who used AR with students who did not use AR (Moreno-Guerrero et al, 2020;Tarng et al, 2022;Tsai, 2020). Previous study stated differences in student learning motivation between classes and learners in AR and control class, especially in anxiety (Chang et al, 2016;Omurtak & Zeybek, 2022). The study also found that AR effectively increases student motivation.…”
Section: The Effect Of Ar Implementation On Learning Motivationsupporting
confidence: 88%
“…These findings are in line with the research of which found that there were differences in the learning motivation of students who used AR with students who did not use AR (Moreno-Guerrero et al, 2020;Tarng et al, 2022;Tsai, 2020). Previous study stated differences in student learning motivation between classes and learners in AR and control class, especially in anxiety (Chang et al, 2016;Omurtak & Zeybek, 2022). The study also found that AR effectively increases student motivation.…”
Section: The Effect Of Ar Implementation On Learning Motivationsupporting
confidence: 88%
“…the experimental and control group students were examined, a statistically significant difference was found between the groups, and this difference was in support of the experimental group (p<0.001). Similar results are found when the literature studies are examined (Kalemkuş & Kalemkuş, 2022;Omurtak & Zeybek, 2022). Peder Alagöz (2020) found a higher enhancement in the academic achievement of the experimental group in the study using AR applications at the seventh-grade level and in the unit of the particulate nature of matter.…”
Section: Determining the Effect Of Ar Applications On Academic Achiev...supporting
confidence: 72%
“…Among them, 11 studies adopted quantitative non-randomized research designs (Al-Muqbil, 2022; Damopolii et al, 2022;Gnidovec et al, 2020;Gregorcic & Torkar, 2022;Lam et al, 2023;Nurhayati et al, 2022;Petrov & Atanasova, 2020;Sivri & Eroglu, 2022;Stojšić, Ostojić, & Stanisavljević, 2022;Weng et al, 2020a;Yang & Tsai, 2021). An equal number of studies, 11 in total, utilized mixed-method research designs (Celik et al, 2020;Delgado-Rodríguez, Carrascal Domínguez, & Garcia-Fandino, 2023;Erbas & Demirer, 2019;Fuchsova & Korenova, 2019;Kozcu Cakir et al, 2020;Lo et al, 2021;Omurtak & Zeybek, 2022;Serdar Yıldırım, 2021;Yapici & Karakoyun, 2021;Yildirim, 2020;Ziden et al, 2022). Additionally, four qualitative studies were included (Ramli et al, 2022;Sarnat et al, 2019;Gökhan Sontay & Karamustafaoglu, 2021;Wommer et al, 2021), along with two quantitative control randomized (Dehghani, Mohammadhasani, Hoseinzade Ghalevandi, & Azimi, 2023;Maraza-Quispe et al, 2023) and one study employing a quantitative descriptive research design (Mustami et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, four qualitative studies were included (Ramli et al, 2022;Sarnat et al, 2019;Gökhan Sontay & Karamustafaoglu, 2021;Wommer et al, 2021), along with two quantitative control randomized (Dehghani, Mohammadhasani, Hoseinzade Ghalevandi, & Azimi, 2023;Maraza-Quispe et al, 2023) and one study employing a quantitative descriptive research design (Mustami et al, 2019). Furthermore, the selected articles were published in various journals, with two articles each in the following journals: International Journal of Information and Education Technology (Maraza-Quispe et al, 2023;Nurhayati et al, 2022), Journal of Science, Environment and Health Education (Omurtak & Zeybek, 2022;Serdar Yıldırım, 2021), Malaysian Journal of Online Education Technology (Gokhan Sontay & Karamustafaoğlu, 2021;Yapici & Karakoyun, 2021), TEM Journal (Damopolii et al, 2022;Lam et al, 2023), and one article each in Advances in Physiology Education (Gregorcic & Torkar, 2022), Eurasia Journal of Mathematics, Science and Technology Education (Ziden et al, 2022), European Journal of Contemporary Education (Fuchsova & Korenova, 2019), Interactive Learning Environments (Dehghani et al, 2023)…”
Section: Methodsmentioning
confidence: 99%